Evaluation of the Antimicrobial Activity of Simplicia Prepared from Wild and Cultivated Phallus indusiatus - Zikriyani, Hikmah; Dwisatyadini, Mutimanda; Winarni, Inggit; Alifiyah, Na’ilah Insani; Aryanto, Arie; Pertiwi, Primasari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Phallus indusiatus is a macrofungus that has attracted attention because of its nutritional value and reported biological activities, including antimicrobial properties. This study evaluated the antimicrobial activity of wild and cultivated P. indusiatus against Staphylococcus aureus, Escherichia coli, and Candida albicans using the disc diffusion method. Wild samples were collected from Central Java, Indonesia, whereas cultivated samples were obtained from Hong Kong. Simplicia suspensions were prepared in sterile distilled water at a concentration of 100 mg/mL and tested against the selected microorganisms. No inhibition zones were observed in any treatment, indicating that the tested samples did not exhibit detectable antimicrobial activity under the conditions applied in this study. The positive control produced a mean inhibition zone of 32 mm, while no inhibition was observed in the negative control. Gene annotation data from previously generated whole-genome sequencing (WGS) of the wild sample were also reviewed to support the interpretation of the results. The selected annotated genes were mainly associated with cellular metabolism, transcriptional regulation, respiration, and metabolite transport. However, the genomic analysis was limited to a small number of annotated genes and was used only as supporting information. Overall, the findings suggest that aqueous suspensions of P. indusiatus simplicia did not show detectable antimicrobial activity against the tested microorganisms under the experimental conditions employed.